23 Agriculture injuries with a focus on rural roadway safety: a global challenge. (1st September 2016) - Peek-Asa, Corinne
Abstract : Throughout the world, transportation-related injuries are among the leading causes of death for agricultural workers. Rural roadways pose unique risks that contribute to their high fatal crash rate per miles travelled when compared with other types of roads. This presentation will introduce the burden and risk factors for agricultural injuries with a focus on farm equipment safety in different types of global roadway settings. Two case studies will demonstrate the complex factors that contribute to crash risk, ranging from roadway design, to rural population demographics, to traffic safety culture. Effective rural roadway safety requires a multisectoral approach and will require input from all rural roadway users. Prevention and intervention approaches will be discussed within the public health framework, addressing primary, secondary and tertiary prevention and policy, engineering, and educational approaches.